Menstrual cycle effects on attitudes toward romantic kissing - Wlodarski, R; Dunbar, R (Springer Science+Business Media New York, 2013)
Hormonal changes associated with the human menstrual cycle have been previously found to affect female mate preference, whereby women in the late follicular phase of their cycle (i.e., at higher risk of conception) prefer males displaying putative signals of underlying genetic fitness. Past research also suggests that romantic kissing is utilized in human mating contexts to assess potential mating partners. The current study examined whether women in their late follicular cycle phase place greater value on kissing at times when it might help serve mate assess- ment functions. Using an international online questionnaire, results showed that women in the follicular phase of their menstrual cycle felt that kissing was more important at initial stages of a relationship than women in the luteal phase of their cycle. Furthermore, it was found that estimated progesterone levels were a significant negative predictor for these ratings.